원발쇼그렌증후군 환자에서 환경인자의 변화에 따른 안구건조증 지표의 변화 분석 - 박주예; 백혜정; 김동현 (Daihan angwa haghoi jabji, 2023)
목적: 원발쇼그렌증후군 환자에서 습도, 온도, 미세먼지 농도의 변화가 안구건조증 지표에 미치는 변화에 대해 분석하고자 하였다. 대상과 방법: 경과 관찰 동안 동일한 안구건조증 치료제를 사용해 왔으며 2회 이상 경과 관찰이 가능하였던 원발쇼그렌증후군 환자18명의 의무기록을 후향적으로 분석하였다. 각 환자의 Symptom Assessment in Dry Eye (SANDE) 점수, 눈물 분비량, 눈물막파괴시간, 안구표면염색점수, 눈물 오스몰 농도 등을 조사하였고, 환자의 내원 전 1주간의 온도, 습도, 초미세먼지 농도를 공공 데이터를통해 산출하여 안구건조증 지표와의 관련성을 분석하였다. 결과: 환자들의 평균 연령은 57.6 ± 12.4세였으며, 모두 여성이었다. 온도가 높을수록 습도가 높았으며 초미세먼지 농도가 낮은 상관관계를 보였다(p=0.004, 0.006). 높은 습도, 높은 온도, 낮은 초미세먼지 농도군에서 낮은 습도, 낮은 온도, 높은 초미세먼지 농도군에비해 SANDE 점수와 눈물 오스몰 농도가 낮은 경향을 보였다(SANDE: p=0.017, 0.063, 0.049; tear osmolarity: p<0.001, 0.009, 0.001). 다면회귀분석에서 온도와 습도의 변화가 초미세먼지 농도 변화에 비해 눈물 오스몰 농도 변화에 더 민감하게 영향을 미쳤다(p=0.005, 0.012). 결론: 원발쇼그렌증후군 환자에서 온도, 습도, 초미세먼지의 변화에 따라 안구불편감과 눈물 오스몰 농도의 변화를 보였다. 특히 여러안구건조증 지표 중 눈물 오스몰 농도가 환경인자에 의해 민감하게 변화하였다. Purpose: To investigate the effects of humidity, temperature, and fine particulate matter (PM2.5) on dry eye disease (DED) parameters in primary Sjogren's syndrome patients. Methods: We retrospectively analyzed the medical records of 18 primary Sjogren's syndrome patients who underwent DED treatment and had more than two follow-up visits. Symptom Assessment in Dry Eye (SANDE) scores, tear secretion, tear film breakup times, ocular surface staining scores, and tear osmolarity were assessed. Temperature, humidity, and PM2.5 concentrations during the week before the patient visits were calculated using public data and their relationships with DED parameters were analyzed. Results: All patients were females, with an average age of 57.6 ± 12.4 years. High temperature was significantly correlated with humidity and PM2.5 concentration (p = 0.004 and = 0.006, respectively). The high humidity, high temperature, and low PM2.5 groups had lower SANDE scores (p = 0.017, = 0.063, and = 0.049, respectively) and tear osmolarity (p < 0.001, = 0.009, and < 0.001, respectively). Multiple regression analysis showed that temperature and humidity had stronger correlations with tear osmolarity (p = 0.005 and = 0.012, respectively) compared to PM2.5 concentrations. Conclusions: Ocular discomfort and tear osmolarity were correlated with temperature, humidity, and PM2.5 concentrations. Among the DED parameters, tear osmolarity was the most sensitive indicator of exposure to environmental factors. KCI Citation Count: 0